Reliability and validity of the 30-15 intermittent field test with and without a soccer ball - Paulsen, K. M.; McDermott, B. P.; Myers, A. J.; Gray, M.; Lo, W.-J.; Ganio, M. S. (Research Quarterly for Exercise and Sport, 2023)
Objective: The purpose of this study was to examine the reliability and validity of the 30-15 Intermittent Field Test (30-15IFT) with and without a ball.